Analisis Pasal 85 Undang-Undang 45 Tahun 2009 Terhadap Penggunaan Jaring Hela Sebagai Alat Tangkap Ikan - Ramadhan, Rievky Wahyu; Azed, Abdul Bari; Suzanalisa, Suzanalisa (Legalitas: Jurnal Hukum, 2024)
Fisheries crime is a fishing activity carried out by fishermen and is contrary to the code of ethics of irresponsible fishing using prohibited fishing gear that results in damage to the marine ecosystem. Fisheries crime includes malpractice activities in the utilization of fishery resources which are illegal activities. The purpose of this study is to understand and analyze article 85 of Law Number 45 of 2009, whether it is effective enough in reducing the number of uses of haul nets as prohibited fishing gear in East Tanjung Jabung Regency